1991
DOI: 10.1071/ar9911285
|View full text |Cite
|
Sign up to set email alerts
|

The nature of Covalently bound fatty acids in wool fibres

Abstract: The wool fibre contains a fatty acid component which can only be liberated from the fibre by treatment with alcoholic alkali solutions. The major fatty acid from this component has been isolated in quantity and purified. Using GC/MS and NMR, the fatty acid was identified as 18-methyleicosanoic acid. The results obtained from transesterification experiments suggest that the fatty acid is covalently bound to the fibre protein by an ester linkage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 0 publications
1
23
0
2
Order By: Relevance
“…Jones et al (1996) suggested that the 30% difference in bound acids removed by potassium t-butoxide and KOH treatments could be due to $30% of the bound lipid trapped within the protein layer adjacent to the outer surface and edges of the cuticle cell. However, an equally tenable explanation for this observation is that the difference could be due to the inaccessible lipid bound to the surface of cuticle cells underlying cuticle cells at the fibre surface, as suggested by Negri et al (1991), which the surface specific potassium t-butoxide treatment will not be able to access and release. This…”
Section: Conclusion and Broader Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Jones et al (1996) suggested that the 30% difference in bound acids removed by potassium t-butoxide and KOH treatments could be due to $30% of the bound lipid trapped within the protein layer adjacent to the outer surface and edges of the cuticle cell. However, an equally tenable explanation for this observation is that the difference could be due to the inaccessible lipid bound to the surface of cuticle cells underlying cuticle cells at the fibre surface, as suggested by Negri et al (1991), which the surface specific potassium t-butoxide treatment will not be able to access and release. This…”
Section: Conclusion and Broader Discussionmentioning
confidence: 86%
“…Tentative nature of assignments While the assignments of some of the acid species in the ToF-SIMS spectra, Table 1, are tentative, the ToF-SIMS mass spectrometric data does not distinguish between normal, iso or anteiso isomers of acids of the same carbon number, the presence of the dominant anteiso fatty acid 18-methyleicosanoic acid has been confirmed by various independent techniques (Negri et al, 1991). The other odd numbered acids observed in this work may also be 'anteiso' acids like 18-methyleicosanoic acid but even numbered acids have not been classified with respect to any branching in the alkyl chains.…”
Section: Calculated Quantities Of Bound Surface Acids In Untreated Famentioning
confidence: 79%
See 1 more Smart Citation
“…18-MEA levels were found to comprise approximately 50% of total bound FA in surface cleaned wool fabric, lower than the 70% value reported in the literature for raw wool [5]. Wool fabric would be expected to have a modified surface lipid content relative to raw wool, as it has undergone additional processing.…”
Section: Methanolic Hydroxidementioning
confidence: 78%
“…This fatty layer has a thickness ranging from 2 to 10 nm and is accounted for about 70% by 18-methylecoicosanoic acid and the other 30% by other covalently bound fatty acids including palmitic, oleic, stearic and eicosanoic acid (Negri et al, 1991). The active species contained in the plasma lead to a chemical etching oxidising action.…”
Section: Wettabilitymentioning
confidence: 99%